Synthesis and Voltammetric Determination of Pb(II) Using a ZIF-8 Based Electrode - Dinh Quang Khieu; Mai Thi Thanh; Tran Vinh Thien; Nguyen Hai Phong; Duc Hoang Van; Pham Dinh Du; Nguyen Phi Hung (My University, 2018)
Synthesis and Voltammetric Determination of Pb(II) Using a ZIF-8 Based Electrode
Keywords: Pb(II) determination; ZIF-8 Electrode; Voltammetric